Modifying fish gelatin electrospun membranes for biomedical applications: cross- linking and swelling behavior - Padrão, Jorge (2014)
Development of suitable membranes is a fundamental requisite for tissue and biomedical engineering applications. This work presents fish gelatin random and aligned electrospun membranes cross-linked with glutaraldehyde (GA). It was observed that the fiber average diameter and the morphology is not influenced by the GA exposure time and presents fibers with an average diameter around 250 nm. Moreover, when the gelatin mats are immersed in a phosphate buffered saline solution (PBS), they can retain as much as 12 times its initial weight of solution almost instantaneously, but the material microstructure of the fiber mats changes from the characteristic fibrous to an almost spherical porous structure. Cross-linked gelatin electrospun fiber mats and films showed a water vapor permeability of 1.37 ± 0.02 and 0.13 ± 0.10 (g.mm)/(m2.h.kPa), respectively. Finally, the processing technique and cross-linking process does not inhibit MC-3T3-E1 cell adhesion. Preliminary cell culture results showed good cell adhesion and proliferation in the cross-linked random and aligned gelatin fiber mats.